Surgical Treatment of Cervicothoracic Junction Lesions in Children: A Series of 18 Cases - Yanzhen Li; Shengcai Wang; Jun Tai; Qi Zeng; Jie Zhang; Yuanhu Liu; Wentong Ge; Yuzhang Huang; Xuexi Zhang; Qiaoyin Liu; Nian Sun; Chenghao Chen; et al. (Journal of Investigative Surgery, 2022)
Purpose The cervicothoracic junction (CTJ) lesions in children is rare. Surgical treatment for lesions at the cervicothoracic junction is challenging due to the presence of the great vessels and other thoracic structures. There are no criteria that help select a surgical approach to manage cervicothoracic lesions in children so far. This study focuses on the cervicothoracic junction lesions in children(C7-T4) and provides experience for the appropriate surgical approach for them. Methods: This retrospective study enrolled 18 children with cervicothoracic junction lesions who underwent surgical treatment in our Hospital from January 2015 to September 2019. They were evaluated with preoperative CT or MR imaging and diagnosed postoperatively by pathological examination. Results: This study included 2 patients with congenital lesions, 4 patients with benign lesions, and 12 patients with malignant lesions. Lesions with a margin below C7-T3, including benign and malignant tumors could be resected using a simple low anterior cervical approach (LACA). Congenital lesions and benign lesions with a margin below T4 could also be treated with this approach. Two-thirds of the malignant lesions below T4 were resected through the LACA combined with video-assisted thoracoscopic surgery (VATS). 1 patient with malignant lesion extending to T4 was removed by the LACA combined with posterolateral thoracotomy. Conclusions: The lesions at the cervicothoracic junction (C7–T4) in children may be managed with the simple LACA used in most patients. For malignancies extending to the T4 level, LACA and VATS could be performed in combination to resect lesions completely and invasively.